In-vitro antifungal and antibacterial activities of rhizomes extracts of Alpinia galanga and Alpinia conchigera griff - Khan, Farman Ullah; Md. Jaffri, Juliana; Bakhtiar, M. Taher (2013)
Alpinia galanga and Alpinia conchigera are belongs to the Zingiberaceae family, distributed in Asia and particularly in the Southeast Asia. The rhizomes of A. galanga have been extensively used as condiment for flavoring and local medicines for the stomach ache, carminative and treating diarrhea. In traditional medicine A. conchigera has been used to treat illnesses such as muscle pain and to stop bleeding. The aims of this study to evaluate the antifungal and antibacterial activities of A. galanga and A. canchigera on several strains of microbes including those which are associated with skin infection. To determine the antibacterial and antifungal activities of A. galanga and A. conchigera, disc diffusion method was used. The antibacterial and antifungal activities of hexane, dichloromethane and methanolic extracts of A. galanga and A. conchigera have been evaluated against gram positive and gram negative bacteria including multi-drug resistant Staphylococcus aureus (MRSA) and fungi such as Trichophyton rubrum, Microsporum canis and Candida albicans, using daptomycin, streptomycin and nystatin as standards respectively. The hexane and methanol extracts showed significant antibacterial and antifungal activities with the zone of inhibition ranging from 14-26 mm, while MRSA was the most susceptible to the hexane extract of A. conchigera. The MIC of both plant A. galanga and A. conchigera were found 35.61 and 30.5 ug/mL respectively against MRSA.